Evaluation of initial results of naïve HIV-infected patients regarding bone health - Yenilmez, Ercan; Çetinkaya, Riza Aytaç (Journal of Surgery and Medicine, 2019)
Aim: HIV-infected patients have increased risk of osteoporosis due to both HIV and the treatment regimens in HIV. Our aim was to reveal the need of screening for bone health in HIV-infected patients, and to reveal the relationship between indirect serum markers of bone-condition, CD4+ T lymphocyte counts and HIV RNA viral loads and DEXA screening results. Methods: Naïve HIV positive patients over 18 years old who were under follow-up in our hospital between January 2014 and December 2018 were included in this retrospective cohort study. CD4+ T cell counts, HIV RNA viral loads, body mass indexes (BMI), 25 (OH) vitamin D, serum calcium and corrected calcium (cCa) levels and DEXA screening results of these patients were recorded. For statistical analysis and interpretation, e-picos (https://www.e-picos.com) and SPSS (version 20.0; SPSS Inc., Chicago, IL, USA) were used. Results: A total of 101 naive HIV-infected patients were included in the study. Vitamin D levels were within normal limits in only 9 (10.8%) patients, while 42 (50.6%) patients had insufficiency and 32 (38.5%) patients had deficiency. Serum calcium and cCa values were significantly lower in patients with < 40 years of age (P=0.04). According to the T-score assessment in DEXA screening, 19 patients (47.5%) had osteopenia findings in at least one of three regions (femoral neck, total hip and lumbar spine). A total of three male patients (7.5%) had osteoporosis. In terms of viral load, only BMD and T-score in women with viral load > 100,000 IU/mL were significantly lower in lumbar spine (P=0.01 and P=0.01, respectively). In terms of CD4 counts, only Z-scores in only lumbar spine and femoral neck were statistically lower in women with CD4 counts > 200 cells/µl (P=0.04 and P=0.03, respectively). There were not any significant differences in any other groups and region in terms of viral load and CD4 count. None of the factors including high viral load, low CD4 + count, low 25 (OH) vitamin D level or low cCa levels were directly related to T, Z-score and low BMD. Conclusion: Osteopenia and osteoporosis are observed more frequently and at younger ages in HIV-infected patients than in the general population. Since we cannot make any prediction on bone health using one of the indirect markers in serum including 25 (OH) vitamin D levels and Ca levels or viral loads and CD4 counts in HIV-infected patients, BMD screening at younger ages may be beneficial.